DIMENSIONAL RELATIONSHIPS AND GROWTH OF GREEN MUSSEL PERNA VIRIDIS IN KAKINADA BAY - Narasimham, K A (Indian Journal of Fisheries, 2011)
For many aspects of growth, ecology and physiology At is desirable to know the relationship between ’these and other body measurements. The relationship of length to 10 body (measurements in the green mussel Perna viridis (Linnaeus) collected during 1974-76 from a subtidai bed in ’the Kakinada Bay are given in this paper together with information on age and growth of the: species. Shafee (1978) studied the various afflometrie relationships in this species from Madras.